THE EFFECTIVENESS OF USING LYRA PERSONAL ASSISTANT IN IMPROVING STUDENTS’ SPEAKING SKILL - Dila Charisma; Suherman Suherman (Program Studi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Cirebon, 2018)
This study is aimed at knowing whether Lyra Personal Assistant can improve students’ speaking skill and to find out whether using this application can motivate second semester students’ speaking English of English Department at Universitas Muhammadiyah Cirebon. This study used quantitative method which categorized pre experimental research. English Department students at Universitas Muhammadiyah Cirebon were choosen to be population, and the sample were the second semester students who took Speaking subject. Measuring speaking skill, the writer used tests and assesing it using scoring rubic by Arthur Huges, and students’ motivation in speaking English after using Lyra were measured by questionnaire with 17 questions and 4 choice of answers. The result showed that using Lyra Personal Assistant was effective in improving students’ speaking skill, it could be seen from the result of pre-test average score (57.33), and result of post-test average score (74.22) that there was improvement score from pre test and post test., average students’ improvement of speaking skill from pre-test to post-test is 16.89. Based on the result of questionnaire, Lyra Personal Assistant also could motivate the second semester students’ speaking English. Key words: Speaking, Lyra Personal Assistant, Motivation